The Stellar Population and Origin of the Mysterious High-Latitude Star-forming Cloud CG 12 - Getman, Konstantin V; Feigelson, Eric D; Lawson, Warrick A; Broos, Patrick S; Garmire, Gordon P (The Astrophysical journal, 2008)
The mysterious high Galactic latitude cometary globule CG 12 has been observed with the ACIS detector on board the Chandra X-Ray Observatory. We detect 128 X-ray sources, of which half are likely young stars formed within the globule's head. This new population of [unk]50 T Tauri stars and one new embedded protostar is far larger than the previously reported few intermediate-mass and two protostellar members of the cloud. Most of the newly discovered stars have masses 0.2-0.7 M [unk], and 9%-15% have K-band excesses from inner protoplanetary disks. X-ray properties provide an independent distance estimate consistent with CG 12's unusual location [unk]200 pc above the Galactic plane. The star formation efficiency in CG 12 appears to be 15%-35%, far above that seen in other triggered molecular globules. The median photometric age found for the T Tauri population assuming Siess et al. (2000) isochrones is similar to 4 Myr with a large spread of <1-20 Myr and ongoing star formation in the molecular cores. The stellar age and spatial distributions are inconsistent with a simple radiation-driven implosion (RDI) model and suggest either that CG 12 is an atypically large shocked globule or that it has been subject to several distinct episodes of triggering and ablation. We report a previously unnoticed group of B-type stars northwest of CG 12 that may be the remnants of an OB association that produced multiple supernova explosions that could have shocked and ablated the cloud over a 15-30 Myr period. HD 120958 (B3e), the most luminous member of the group, may be currently driving an RDI shock into the CG 12 cloud.